In vivo confocal microscopy study of climatic droplet keratopathy - Urrets Zavalía, Julio Alberto (2012)
Climatic droplet keratopathy (CDK) is a corneal degenerative disease characterized by its progressive opacity because of accumulation of globular deposits in Bowman’s layer (BL) and anterior stroma (AS), as well as abnormal corneal sensitivity. We report herein for the first time the study of three patients each with different grades of CDK using in vivo confocal microscopy (iVCM), a technique that has allowed the measurement of normal and pathological corneal components.